Guide to structural optimization /by the Technical Committee on Optimal Structural Design of the Technical Administrative Committee on Analysis and Computation of the Technical Activities Division of the Structural Engineering Institute of the American Society of Civil Engineers ; edited by Jasbir S. Arora. - Arora, Jasbir S.
Includes bibliographical references and index.